Organizational Contribution to E-business Adoption for SMEs in The World - Sinta Aryani; Yati Rohayati; Asih Aulia Putri; Firza Khalisha Rinjany (International Journal of Innovation in Enterprise System, 2023)
The aim of this study is to identify the issues faced by SMEs all around the world in adopting ebusiness. This is a work of literature study with the classification based on technological,organizational, and environmental (TOE). The study collects 116 articles from various journal portals.The finding of this study is the factors that concerned the most in adopting e-business among theSMEs which are related to the organization. The organization has a contribution of 50% compared totechnology and the environment. Under the organization, human resource is a prominent key to beimproved if the SMEs want to adopt e-business well. This situation applies in the continents of AsiaAmerica, Europe, Australia, and Oceania. Only African SMEs concern more about managementrather than human resources. This study does not consider the interplay between the factors, however,the practical implication of this study is that the finding can be used as input for decision-makers whohave an interest in improving the performance of SMEs or raising the level of SMEs in their region,one of which is by increasing the adoption rate of e-business among SMEs. Further, there is anopportunity for future research in investigating the strength of the relationship in each factor to theadoption of e-business, or even in between factors. The contribution of this study is to providethorough synopsis regarding the factors that need to be considered by the SMEs if they want to adopte-business.